Hypertension attenuates the link of osteoprotegerin to reduced baroreflex sensitivity in type 2 diabetes mellitus patients on oral antidiabetic and antihypertensive therapy – a cross sectional study - A. Naga Sailaja; Nivedita Nanda; B. S. Suryanarayana; G. K. Pal (BMC Endocrine Disorders, 2022)
Abstract Purpose Decreased baroreflex sensitivity (BRS) has been shown to be a marker of cardiovascular (CV) risk. In the present study, the difference in CV risk biomarkers in type 2 diabetes (T2D) patients receiving oral antidiabetic drugs (OAD) with and without hypertension has been assessed. Materials and methods Ninety-two T2D patients on OAD without hypertension (control group) and eighty-eight diabetic patients with hypertension on OAD and antihypertensive drugs (test group) matched for age, gender, body mass index, serum glucose, glycated haemoglobin, and duration of the disease were recruited for the study. Their blood pressure (BP) variability including BRS, heart rate variability (HRV), insulin, lipid profile, osteoprotegerin (OPG), and tumor necrosis factor-α (TNF-α) were estimated. The association of various factors with BRS was assessed by Spearman correlation and multiple regression analysis. Results BRS was decreased (13.90 ± 5.27 vs 6.76 ± 4.58), HRV sympathetic indices [LFnu, LF-HF ratio (1.30 ± 0.49 vs 1.93 ± 0.62)], HOMA-IR, atherogenic index of plasma (AIP), OPG (223.08 ± 103.86 vs 287.60 ± 121.36) and TNF-α were increased, and parasympathetic indices [TP (1012.90 ± 316.18 vs 625.88 ± 229.84), RMSSD, SDNN, NN50, pNN50] were decreased in the test group compared to control group. In control group, parasympathetic indices, AIP, OPG, and TNF-α had a significant correlation and OPG had an independent association (β − 0.344; p 0.004) with BRS. In test group, BP, LF-HF ratio, parasympathetic indices, AIP, OPG, and TNF-α had significant correlation, and TNF-α alone (β − 0.297; p 0.022) had an independent contribution to decreased BRS. Conclusion Despite antidiabetic and antihypertensive treatments, T2D patients with hypertension had more cardiometabolic risks in comparison to normotensive T2D patients. Inflammation could be the inciting factor for rise in BP and decrease in BRS (CV risk) in hypertensive T2D patients. Hypertension in diabetes could attenuate the link of OPG to the reduction in BRS. Reduction in BRS could be a physiological marker of CV risk in T2D patients treated with OAD.